PEMANFAATAN MEDIA DARING GOOGLE FORM DALAM PROSES PEMERINTAHAN PEKON SUKA MAJU, KEC. NGARAS, KAB. PESISIR BARAT, PROV.LAMPUNG - Intan Putri; Leti Karmila; Ahmad Iman Mulyadi; Selly Pitri Yani (Universitas Sumatera Selatan, 2022)
Internet technology in today's era is growing and growing rapidly. The increase in technology has an impact on society. One of the developments that is quite influential for society is the internet. The Internet has grown into a tool of information and communication that cannot be ignored. With the internet, human life is easier. This rapid technological advancement provides convenience in people's lives and cannot be separated from the increasingly widespread internet network. In addition, with the development of technology, it is easier for the community to do work, especially for the village government, the development of technology that is integrated with the internet has an important role and helps in data management/collection. There are many applications that can be used to support data management for the government or Pekon devices that are online-based and free. One of the software that is easily accessible, free to use, simple in operation and good enough to be used as a medium for data collection is Google Form. The research method used is descriptive qualitative with analytical methods. This research activity was carried out in Suka Maju Village, district. Ngaras district. West coast of Lampung. This location was chosen as the focus of research so that the authors can conduct research more carefully, focused and easy to obtain the data and information needed. The research was conducted in July-August 2022. The data collection techniques were: Interview, Observation, Document.The results showed that almost all of the informants said that they did not know what a goggle form was, this shows that public knowledge about the google form is very minimal. Even though Google Forms are really needed by Pekon devices like to advance in this era. Here it can be seen from the data from interviews that have been carried out by the author that their education level is still low so that it affects the level of knowledge, it is not surprising that they do not have knowledge of the google form media. So the majority of Pekon devices like to go forward saying they want and want to learn about the google form, they are very enthusiastic and happy with the E-Rediness program, which is discussing the google form.